2005
DOI: 10.1111/j.1467-8624.2005.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Face Processing in Infancy: Developmental Changes in the Use of Different Kinds of Relational Information

Abstract: Adults use both first-order, or categorical, relations among features (e.g., the nose is above the mouth), and second-order, or fine spatial relations (e.g., the space between eyes), to process faces. Adults' expertise in face processing is thought to be based on the use of second-order relations. In the current study, 5-month-olds detected second-order changes, but 3-month-olds failed to detect second-order changes induced by 2 different manipulations. Three-month-olds did detect first-order changes, however.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
140
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 63 publications
(136 reference statements)
12
140
4
Order By: Relevance
“…Bhatt, et al, 2005;Otsuka et al, 2007;Turati, Sangrigoli, Ruely, & de Schonen, 2004) and adults (e.g. Yin, 1969).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhatt, et al, 2005;Otsuka et al, 2007;Turati, Sangrigoli, Ruely, & de Schonen, 2004) and adults (e.g. Yin, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…The development of face perception and recognition during infancy has been studied extensively including both the role of experience (Kelly et al, 2007;Kelly et al, 2009;Pascalis, de Haan, & Nelson, 2002) and the aspects of visual information that infants use (Bhatt, Bertin, Hayden, & Reed, 2005;Cohen & Cashone, 2001;Hyden, Bhatt, Reed, Corbly, & Joseph, 2007;Quinn & Tanaka, 2009). However, there are relatively few studies testing the effect of contrast polarity of faces in infants.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that, although sensitivity to first-order relations is available by 3 months or earlier, sensitivity to second-order information may not develop until sometime between 3 and 5 months of age (Bhatt et al, 2005). Despite of evidence of second-order relational processing in infants, the authors concluded that significant developmental changes occur in later years until adult-like face expertise is achieved (Bhatt et al, 2005).…”
Section: Face Processing In Infantsmentioning
confidence: 73%
“…Despite of evidence of second-order relational processing in infants, the authors concluded that significant developmental changes occur in later years until adult-like face expertise is achieved (Bhatt et al, 2005).…”
Section: Face Processing In Infantsmentioning
confidence: 99%
See 1 more Smart Citation